Financial Liberalization, Foreign Direct Investment and Economic Growth: A Dynamic Panel Data Validation - Saif Eddine Ayouni; Fakhri Issaoui; Salem Brahim (International Journal of Economics and Financial Issues, 2014)
The aim of this study is to show that financial liberalization, as a determinant of financial development, can stimulate the relationship between foreign direct investment (FDI) and economic growth. Two distinct components have been analyzed. The first one is a theoretical component in which we tried to treat the relationship between financial development, internal financial liberalization, and FDI using an endogenous growth model. The second component consists of an empirical study which tried using a panel data to validate the previously stated theoretical relationship. The survey, covering a sample of sixty nine developed and developing countries enabled us to reach three fundamental results. First, when financial systems are non-liberalized, we have noted that FDIs had a negative effect on GDP growth per capita. Second, when FDI are implemented in countries characterized by their developed financial sector they generate positive effects on growth. This implies that the key variable which determines FDI efficiency is the degree of financial systems liberalization. Consequently, in non-liberalized financial systems FDI effects on growth are challenged. Third, we showed that financial development level is a strategic variable which positively affects growth.